2010
DOI: 10.2174/157015910791233204
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin Biology and Nervous System

Abstract: Our understanding of the movement of water through cell membranes has been greatly advanced by the discovery of a family of water-specific, membrane-channel proteins: the Aquaporins (AQPs). These proteins are present in organisms at all levels of life, and their unique permeability characteristics and distribution in numerous tissues indicate diverse roles in the regulation of water homeostasis.Phenotype analysis of AQP knock-out mice has confirmed the predicted role of AQPs in osmotically driven transepitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 100 publications
0
17
0
Order By: Relevance
“…The functions of AQPs in the central nervous system seem to be diverse; studies have shown a role for AQPs in bidirectional transport of water between brain and blood vessels, in cerebrospinal fluid formation, in neural signal transduction, in osmoreception, and in some brain pathologies such as brain edema, brain tumors, and autism (reviewed in refs. 8,44). Given that AQP7 also facilitates glycerol transport, it might have a role in the energy metabolism of neurons, as was previously found with respect to AQP9.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The functions of AQPs in the central nervous system seem to be diverse; studies have shown a role for AQPs in bidirectional transport of water between brain and blood vessels, in cerebrospinal fluid formation, in neural signal transduction, in osmoreception, and in some brain pathologies such as brain edema, brain tumors, and autism (reviewed in refs. 8,44). Given that AQP7 also facilitates glycerol transport, it might have a role in the energy metabolism of neurons, as was previously found with respect to AQP9.…”
Section: Discussionmentioning
confidence: 52%
“…The hypothesis that this mutation has functional relevance was earlier supported by the findings of Kondo et al, 20 who could not show any association between the presence of the mutation and the occurrence of obesity or type 2 diabetes; however, they did find the first homozygous G264V subject with impaired plasma glycerol release from fat tissue after exercise tests, although urine glycerol levels were not determined. AQPs as a family have a conserved structure, 8,32 existing in membranes as homotetramers. Each subunit monomer forms a separate permeable pore composed of six α-helix transmembrane domains with inverted symmetry between the first and last three domains, and a poreforming loop with the signature NPA motif.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AQP4 is further expressed at sites of ependymal cells in contact with the brain-cerebrospinal fl uid barrier. Th is expression pattern indicates that AQP4 is involved in water homeostasis in the brain (69). Phenotype analysis of transgenic mice lacking Aqp4 gene has provided evidence of other roles of this aquaporin, such as the involvement in brain oedema, in glial cell migration and in neuronal signal transduction (68).…”
Section: Aqp4: Brain Functionmentioning
confidence: 99%
“…In particular, AQP4 facilitates clinically important water movement into and out of the brain in the development and resolution of brain oedema and modulation of AQP4 expression or function is also predicted to modulate glial scar formation, which may be of clinical utility in traumatic injury, tumour and infection. Moreover, recent data suggest an increase in extracellular space volume in AQP4 defi ciency and an impaired K + reuptake by AQP4-null astrocytes, which may be related to functional signifi cant AQP4-K + channel interactions (69). It is interesting to note the fi rst case report of a patient with anti-AQP4 antibody who presented with recurrent hypersomnia as the main symptom, symmetrical hypothalamic lesions as well as a reduced orexin (hypocretin) level in the cerebrospinal fl uid RevIew (70).…”
Section: Aqp4: Brain Functionmentioning
confidence: 99%